Experimental measurement of transversal micro‐ and macro permeability during compression molding of PP/Glass composites. Issue 1 (31st August 2013) - Gennaro, R.; Christmann, M.; Greco, A.; Rieber, G.; Mitschang, P.; Maffezzoli, A.
<x xml:space="preserve">Abstract</x> In this work, a new experimental method is presented, aimed to measure the transversal permeability of fabric reinforcements for composite production. Through‐thickness impregnation of a glass woven fabric with polypropylene matrix was studied during compression molding experiments. The composite thickness was continuously measured during compression molding at different temperatures and pressure levels. The measured composite thickness was used to evaluate the molten front advancement during fabric impregnation. The existence of two different mechanisms of impregnation was highlighted by changes in the slope of the molten front advancement. Optical microscopy confirmed the occurrence of these two different mechanisms: macro‐scale impregnation, associated to void reduction between the bundles (inter‐bundle) occurring at lower times, and micro‐scale impregnation, associated to the flow of the matrix inside each bundle (intra‐bundle), occurring at longer times. Each of the two processes is characterized by a different value of the permeability, calculated according to Darcy law. The intra‐bundle and inter‐bundle permeability were used for calculating the transversal global permeability applying the Papathanasiou model. These values were compared with transversal permeability results evaluated using a low viscosity test fluid. POLYM. COMPOS., 35:105–112, 2014. © 2013 Society of Plastics Engineers